2021
DOI: 10.1136/annrheumdis-2021-eular.3159
|View full text |Cite
|
Sign up to set email alerts
|

Pos0872 clinical Features and Outcome of 1054 Patients With Systemic Sclerosis: An Analysis of the Portuguese REUMA.PT Registry for Scleroderma (REUMA.PT/SSC)

Abstract: Background:Systemic sclerosis (SSc) may present distinctive manifestations and survival in different ethnic and geographic groups.Objectives:To describe the clinical features, treatments, and survival of adult SSc patients registered in Reuma.pt/SSc.Methods:Demographic features, SSc subsets, fulfilment of classification criteria, clinical and immunologic characteristics, comorbidities, medication and deaths were reviewed. Survival was calculated for patients included in the registry within the first 2 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 2022, in 1054 SSc Portuguese patients, Freitas et al identified preclinical SSc in 13% and ssSSc in 3.3%, as well as puffy fingers in 62.1% dSSc and 47.3% lSSc ( P < 0.01). It is important to highlight that the authors did not provide the definition of preclinical SSc neither addressed the VEDOSS criteria in their work to identify very early patients [18].…”
Section: The Myth Of Sine Scleroderma Systemic Sclerosismentioning
confidence: 99%
“…In 2022, in 1054 SSc Portuguese patients, Freitas et al identified preclinical SSc in 13% and ssSSc in 3.3%, as well as puffy fingers in 62.1% dSSc and 47.3% lSSc ( P < 0.01). It is important to highlight that the authors did not provide the definition of preclinical SSc neither addressed the VEDOSS criteria in their work to identify very early patients [18].…”
Section: The Myth Of Sine Scleroderma Systemic Sclerosismentioning
confidence: 99%
“…Several SSc registries have been developed around the world; they contribute to improving the knowledge about rare and complex diseases and help in the management and follow-up of patients. 1,2,[8][9][10][11][12][13][14][15] Such registries can also facilitate research into rare diseases like SSc and can be considered as a prerequisite to selecting uniform cohorts of patients to be potentially included in clinical studies with similar criteria for outcome measurement. 1,4 Nevertheless, studies have revealed heterogeneity of the disease presentations, phenotype, and clinical variants among populations (gender, geographical, partly due to genetic and ethnic heterogeneity).…”
Section: Introductionmentioning
confidence: 99%